Acetone Sensing Properties and Mechanism of Rh-Loaded WO3 Nanosheets - Qiu, Zhilei; Hua, Zhongqiu; Li, Yan; Wang, Mengjun; Huang, Dan; Tian, Chen; Zhang, Chensheng; Tian, Xuemin; Li, Erping (Frontiers in Chemistry, 2018)
WO3 nanosheets was prepared by an acidification method and the Rh catalyst was dispersed on the surface of the nanosheets with a wet impregnation method. The morphology of pristine WO3 and Rh modified WO3 nanosheets and their responses to acetone gas were studied. According to oxygen adsorption combined with TPR results, the sensing and sensitization mechanism of acetone were discussed. It was found that no visible changes in nanostructures or morphologies were observed in WO3 nanosheets with Rh, however, the sensor resistance and sensor response were greatly promoted. The basic sensitization mechanism could be caused by the electronic interaction between oxidized Rh and WO3 surface.